O13.1 The Use of Rapid Epidemic Appraisals For Planning and Scaling Up Focused HIV Prevention Programmes For Female Sex Workers in Nigeria. (13th July 2013) - Ikpeazu, A; Daniel, U; Momah, A; Ameyan, W; Mari, B Madu; Akala, F A; Blanchard, J
Abstract : Background: The HIV epidemic in Nigeria is complex with substantial heterogeneity in its distribution across different regions and diverse factors that drive the epidemic. Therefore, it is critical that HIV prevention programmes and strategies match the local context and that resources are allocated to interventions with the greatest impact. Nigeria's National Agency for the Control of AIDS (NACA) is coordinating a large-scale initiative to conduct rapid epidemic appraisals across most states, including the mapping and size estimates of female sex workers (FSWs). Seven states have completed the appraisal of FSWs, and are now planning programmes accordingly. Methodology: Mapping was done using a two-level process of identifying and validating locations where FSWs solicit and/or meet clients. The first level involved conducting interviews with secondary key informants to collect information on the location and profile of hotspots, size estimates and typology of FSWs. The second level was done by interviewing primary key informants (FSWs themselves) at each hotspot to validate the information collected and generate more detailed information. Results: A total of 10, 233 hotspots were identified across the states and 126, 489 FSWs {Hotel/Lodge (29.6%) Bar/Nightclub (30%), Home based (4.1%), Brothel (14.6%) and Street based (16.6%)} were mapped. There was substantial variability in the population density of FSWs (per thousand adult men) across the states ranging from 17 in Abuja to 2 in Anambra. Furthermore, there were clear differences in the density of FSWs per spot with the mean number of FSWs/spot ranging from 17 in Abuja to 8 in Ondo. Conclusion: The FSW population in Nigeria is large and diverse, with substantial differences between and within states with respect to the population size, density and organisational typologies of sex work. This information is central to Nigeria's planning process for scaling up focused HIV prevention programmes and services.